Regression models to assess the thermal performance of Brazilian low-cost houses: consideration of solar incidence and shading devices - Anchieta, Camila Chagas (2016)
Building performance simulation (BPS) tools are significant and helpful during all design stages, especially during the early ones. However, there are obstacles to the full implementation and use of such tools, causing them not to become an effective part of the design process. In order to overcome this barrier, this research is presented, with the creation of regression models (meta-models) that allow to predict the discomfort by heat and/or by cold in a Brazilian low-cost house (LCH) in three distinct bioclimatic zones in Brazil, represented by the cities of Curitiba/PR, São Paulo/SP and Manaus/AM. The focus of this work was to analyze the impact of solar incidence and shading devices on thermal comfort by applying the meta-models. The method consisted in a) collecting data from projects referring to the type of building aforementioned to aid in the creation of the base model; b) definition of the key parameters and their ranges to be varied; c) simulations run on EnergyPlus using the Monte Carlo method to randomly create parameters combinations within their defined ranges; d) regression analysis and metamodels elaboration, followed by their validation with reliability tests; and lastly, e) a case study, consisting in applying the meta-models to a standard LCH to verify the impact of shading devices in a unit in regards to thermal comfort and the their potential as support tool in the design process. In general, all R2 values for the meta-models were above 0.95, except for the ones for São Paulo and Curitiba for discomfort by heat, 0.74 and 0.61, respectively. In regards to the case study, the meta-models predicted a decrease of approximately 50% in discomfort by heat for Manaus when a given combination of orientation, quantity and size of the devices was used. For the remaining locations, the meta-models predicting discomfort by heat and by cold require further investigation to properly assess some unexpected predictions and the meta-models sensitivity to the parameters related to shading devices.